Analisis Kepuasan Pengunjung Terhadap Pelayanan Wisata Pantai Tan Sirdano Kabupaten Pesisir Selatan Menggunakan Customer Satisfaction Index Dan Importance Performance Analysis - Indri Putri Pratama; Helma Helma (UNIVERSITAS NEGERI PADANG, 2019)
Abstract–Tourism is one sector that has a positive impact an economic development. Tan Sirdano Beach is one of tourism destination in Pesisir Selatan District. In developing Tan Sirdano Beach tourism, a marketing strategy based on visitor satisfaction is needed. However the services that provided by manager have not made the visitors satisfied. The purpose of this research to find level of visitor satisfaction based on Customer Satisfaction Index (CSI) and visitors’ desire from each attribute based on Importance Performance Analysis (IPA). This research used primary data with 100 questionnaires that is shared to the visitors of Tan Sirdano Beach who had visited at least 2 times. The result from this research that level of visitor satisfaction overall is 70.12% in the range of values 66% - 80.99% which indicates that the visitor satisfaction index is a